The GitHub Effect. - Grier, David Alan (Computer (00189162), 2015)
Although GitHub has become a great tool for studying the software development process, it poses afundamental problem to those who study work. The Web extra at http://youtu.be/z7aiYedJr8w is an audio recording of author David Alan Grier expanding on his Errant Hashtag column, in which he talks about how GitHub has become a great tool for studying the software development process but poses a fundamental problem to those who study work.